2010
DOI: 10.1111/j.1365-2966.2009.16014.x
|View full text |Cite
|
Sign up to set email alerts
|

Localizing the VHE γ-ray source at the Galactic Centre

Abstract: The inner 10 pc of our Galaxy contains many counterpart candidates of the very high energy (VHE; >100 GeV) γ-ray point source HESS J1745−290. Within the point spread function of the H.E.S.S. measurement, at least three objects are capable of accelerating particles to VHE and beyond and of providing the observed γ-ray flux. Previous attempts to address this source confusion were hampered by the fact that the projected distances between these objects were of the order of the error circle radius of the emission c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…The source of the GeV and TeV γ-rays is not variable and it is not clear if the emission comes from the vicinity of the black hole, if it is produced in an extended region around the black hole, or, finally, if it comes from an unrelated source positionally coincident with the supermassive black hole in Sgr A*. The best positional uncertainty of 6 on TeV source HESS J1745-303 (Acero et al 2010) still allows several sources to be responsible for the observed very high energy(VHE) emission: the central black hole itself (Aharonian & Neronov 2005a), a plerion within several arcseconds from the GC (Wang et al 2006;Hinton & Aharonian 2007), a putative black hole plerion around Sgr A* (Atoyan & Dermer 2004), and the central diffuse region around the GC (Aharonian & Neronov 2005b;Ballantyne et al 2007;Chernyakova et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The source of the GeV and TeV γ-rays is not variable and it is not clear if the emission comes from the vicinity of the black hole, if it is produced in an extended region around the black hole, or, finally, if it comes from an unrelated source positionally coincident with the supermassive black hole in Sgr A*. The best positional uncertainty of 6 on TeV source HESS J1745-303 (Acero et al 2010) still allows several sources to be responsible for the observed very high energy(VHE) emission: the central black hole itself (Aharonian & Neronov 2005a), a plerion within several arcseconds from the GC (Wang et al 2006;Hinton & Aharonian 2007), a putative black hole plerion around Sgr A* (Atoyan & Dermer 2004), and the central diffuse region around the GC (Aharonian & Neronov 2005b;Ballantyne et al 2007;Chernyakova et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Detailed studies of the position of the source with the high-angular resolution of H.E.S.S. has provided the most accurate position to date (192): the source is within 8 ±9 stat ±9 sys from the position of Sgr A with an upper limit on the extension of the source of 1.3' (95% confidence level). This measurement rules out the SNR Sgr A East as a source of the gamma-ray emission, leaving two main objects as possible astrophysical counterparts: the supermassive black hole Sgr A or the pulsar wind nebula PWN G359.95-0.04 (193).…”
Section: Use Case: the Galactic Center Regionmentioning
confidence: 99%
“…1). The position of the HESS J1745-290 centroid is coincident with Sgr A* and the pulsar wind nebula G359.95-0.04 positions within 13 [3]. The energy spectrum of HESS J1745-290 derived from 10 year observations with H.E.S.S.…”
Section: A Strong Tev Emission From the Galactic Centermentioning
confidence: 99%